Chemical Composition, Essential Oil Characterization and Antibacterial activity of Cumin (Cuminum Cyminum) - Iram, Naila; Edwin, Elishma Cedric (Pakistan BioMedical Journal, 2022)
Family apiaceae, an important source of bioactive compounds, used for the treatment of many diseases since ages. Objective: Present study was conducted to explore active components of Cuminum Cyminum essential oil. Endeavor of the current study was to investigate the phytochemical contents and antibacterial assessment of essential oil against gram positive and negative bacteria. Method: Essential oil was extracted from seeds by hydrodistillation, dried and stored at -4oC. physical and chemical characterization was done. Antibacterial activity was also determined. Results: GC-MS analysis revealed major components cuminal 35%, γ-terpinene 32%, α-terpinene-al 7%, γ-terpinene 4.45%, daucene 4.3%, and trans-caryophyllene 5.342%, some trace components like myrcene 0.12%, 1-8 cineole, and γ-terpinene-7-al were also present. Conclusion: Chemical components (cuminal, turpentine, daucene, caryophyllene) present in cumin essential oil is responsible for its biological activities.